2021
DOI: 10.1186/s11689-021-09358-1
|View full text |Cite
|
Sign up to set email alerts
|

FOXP1 syndrome: a review of the literature and practice parameters for medical assessment and monitoring

Abstract: FOXP1 syndrome is a neurodevelopmental disorder caused by mutations or deletions that disrupt the forkhead box protein 1 (FOXP1) gene, which encodes a transcription factor important for the early development of many organ systems, including the brain. Numerous clinical studies have elucidated the role of FOXP1 in neurodevelopment and have characterized a phenotype. FOXP1 syndrome is associated with intellectual disability, language deficits, autism spectrum disorder, hypotonia, and congenital anomalies, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Disruption of the FOXP1 locus results in a collection of cognitive and neurodevelopmental symptoms known as FOXP1 syndrome (Lozano et al ., 2021; Siper et al, 2017). The individuals diagnosed with this disorder have loss of function mutations such as deletions, frameshifts or de novo point mutations in one copy of FOXP1 (Siper et al, 2017; Urreizti et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the FOXP1 locus results in a collection of cognitive and neurodevelopmental symptoms known as FOXP1 syndrome (Lozano et al ., 2021; Siper et al, 2017). The individuals diagnosed with this disorder have loss of function mutations such as deletions, frameshifts or de novo point mutations in one copy of FOXP1 (Siper et al, 2017; Urreizti et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A crucial regulator of the molecular mechanisms underlying cortical development is the transcription factor (TF) Forkhead Box P1 (FOXP1). FOXP1 has been linked to neurodevelopmental disorders, such as autism spectrum disorder (ASD) and intellectual disability (ID) (Co et al, 2020; Lozano et al, 2021). Previous studies have shown that either knockdown (KD) or knockout (KO) of FOXP1 leads to varying phenotypes reflecting abnormal neurogenesis in the cortex (Braccioli et al, 2017; Li et al, 2015; Pearson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Children and adults with FOXP1 syndrome present with behavioral symptoms that often include externalizing behaviors (i.e., hyperactivity or impulsivity), anxiety, and autistic traits. FOXP1 syndrome is also associated with medical problems such as heart defects (22–40%), recurrent infections (e.g., sino-respiratory infections, skin infections) (33–67%), genitourinary abnormalities (13–42%), gastrointestinal problems (44–73%), and ocular defects (56–75%) [ 11 , 29 , 30 ]. Neurological abnormalities can include dysarthria, hypotonia, gait problems, feeding issues, atypical neuroimaging findings, and seizures [ 11 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…ERK activation through downstream signaling guides to changes in the cytoskeletal organization, which ultimately leads to the stimulation of neurite outgrowth [ 62 , 63 ]. The FOXP1 gene, which was hypomethylated in FXSA, compared to TD, encodes for a transcription factor important for early brain development and, interestingly, variants, deletions, missense mutations FOXP1 are causative for severe forms of ASD, often comorbid with intellectual disability, language deficits, and congenital anomalies, including mild dysmorphic features, and brain, cardiac, and urogenital abnormalities [ 64 ].…”
Section: Discussionmentioning
confidence: 99%